Childfree Persfektif Al-Qur’an: Studi Penafsiran Buya Hamka Terhadap Konsep Rezeki Anak dalam Tafsir Al-Azhar - Yarsha Ardhana Harahap; Agusman Damanik; Hery Sahputra (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2026)
The childfree phenomenon in contemporary Muslim communities demonstrates a shift in family orientation that challenges the normative construction of offspring as an integral part of religious life, particularly when linked to the concept of children’s sustenance in the Qur’an, which has been understood within established theological and social frameworks. This study aims to examine in depth Buya Hamka’s interpretation in Tafsir al-Azhar regarding the concept of children’s sustenance and assess its conceptual relevance in responding to the childfree discourse that is developing in modern society. A qualitative approach based on literature studies is used, employing thematic interpretation methods to trace verses related to sustenance and offspring, and is then analyzed using an interpretative-critical approach to identify Hamka’s argumentation patterns and epistemological orientations. The results of the study show that the construction of children’s sustenance in the Qur’an not only refers to material security but also reflects the relationship of human existential dependence on God, encompassing spiritual, ethical, and social dimensions in an integrated manner. Hamka’s interpretation displays a rational-religious character that emphasizes the balance between human endeavor and belief in the guarantee of sustenance, while simultaneously criticizing the reduction of sustenance’s meaning to mere economic calculations. In the context of childfree life, this framework demonstrates the tension between modern rationality, grounded in life planning, and the theological paradigm regarding the blessings of offspring and the family’s moral responsibility. The implications of this study enrich contemporary exegetical discourse through a contextual reading of the verses about sustenance and offer a conceptual foundation for formulating Islam’s position on childfree choices in a more proportionate, reflective, and argumentative manner.